2003
DOI: 10.1046/j.1365-313x.2003.01903.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical maps and recombination frequency of six rice chromosomes

Abstract: These authors contributed equally to this work. SummaryWe constructed physical maps of rice chromosomes 1, 2, and 6±9 with P1-derived arti®cial chromosome (PAC) and bacterial arti®cial chromosome (BAC) clones. These maps, with only 20 gaps, cover more than 97% of the predicted length of the six chromosomes. We submitted a total of 193 Mbp of non-overlapping sequences to public databases. We analyzed the DNA sequences of 1316 genetic markers and six centromere-speci®c repeats to facilitate characterization of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 40 publications
11
120
1
Order By: Relevance
“…We exploited the pseudomolecule of chromosome 3B (Choulet et al 2014) as well as high-throughput detection of SNPs (Rimbert et al 2017) to map 252 CO events in intervals of ,26 kb using genotyping data. This resolution has never been reached in wheat before and was close to the one observed for the four hotspots described in rice (Wu et al 2003). In the collared flycatcher, a songbird species, 279 COs were localized within intervals of ,10 kb (Smeds et al 2016) which was only 1.8 times more compared to our analysis (156 COs) while the wheat genome is 17 times larger.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We exploited the pseudomolecule of chromosome 3B (Choulet et al 2014) as well as high-throughput detection of SNPs (Rimbert et al 2017) to map 252 CO events in intervals of ,26 kb using genotyping data. This resolution has never been reached in wheat before and was close to the one observed for the four hotspots described in rice (Wu et al 2003). In the collared flycatcher, a songbird species, 279 COs were localized within intervals of ,10 kb (Smeds et al 2016) which was only 1.8 times more compared to our analysis (156 COs) while the wheat genome is 17 times larger.…”
Section: Discussionsupporting
confidence: 87%
“…New wheat-genomic tools allow more resolute analysis of recombination pattern Whole-genome, fine-scale recombination studies in plants have only been conducted in species for which the genome sequence was available (Wu et al 2003;Liu et al 2009;Paape et al 2012;Rodgers-Melnick et al 2015;Shilo et al 2015). However, this mainly restricted such analyses to species with small and compact genomes with low rates of TEs.…”
Section: Discussionmentioning
confidence: 99%
“…The peak of both QTLs corresponded to the previously mapped position of the mutant locus, brown pericarp, Rc (Kinoshita, 1998 Figure 1B, i). The genetic/ physical distance in this region averages 1.4 Mb/cM, much above the genome average of 200 to 250 kb/cM, as expected for a pericentromeric region (Zhao et al, 2002;Wu et al, 2003). An investigation of the genotype-phenotype relationship in 285 BC2F2 families demonstrated that all 18 families with red grain contained the O. rufipogon allele at either RM125 or the adjacent marker, RG30, suggesting that the gene underlying rg7.1 lay between these two markers.…”
Section: Rough Mapping Of Qtls and The Rc Mutantmentioning
confidence: 68%
“…Crossing-over in the (peri-)centromeric regions, which may account for as much as 50% of the chromosome length, is essentially suppressed [23,36-40]. In genomes with smaller chromosomes, such as rice and Arabidopsis, cross-over suppression at the centromere is restricted within a relatively small region [4,41,42]. Like rice and Arabidopsis, the region of recombination suppression on chromosome 2 is also restricted to a relatively small region corresponding to ~30% of the chromosome length.…”
Section: Discussionmentioning
confidence: 99%